1999
DOI: 10.1097/00007890-199911150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Contractile Sequelae of Rat Intestinal Ischemia/Reperfusion Injury1

Abstract: I/R injury evokes a molecular and cellular inflammatory response within the intestinal muscularis that is associated with a subsequent decrease in intestinal motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 38 publications
6
78
1
2
Order By: Relevance
“…23 The paradigm of the present study and our previous work is that inflammatory events within the muscularis externa, caused by intestinal handling, directly modulate smooth muscle contractile activity and subsequently changes in transit. 5,6,8,24 Similar to our reported observations in the small intestine, the data from the present study confirm an association between surgical trauma, leukocyte infiltration, and smooth muscle dysfunction within the colonic muscularis. Based on this and our previous work, we propose that activated resident as well as recruited leukocytes release kinetically active mediators that directly modulate motility.…”
Section: Discussionsupporting
confidence: 91%
“…23 The paradigm of the present study and our previous work is that inflammatory events within the muscularis externa, caused by intestinal handling, directly modulate smooth muscle contractile activity and subsequently changes in transit. 5,6,8,24 Similar to our reported observations in the small intestine, the data from the present study confirm an association between surgical trauma, leukocyte infiltration, and smooth muscle dysfunction within the colonic muscularis. Based on this and our previous work, we propose that activated resident as well as recruited leukocytes release kinetically active mediators that directly modulate motility.…”
Section: Discussionsupporting
confidence: 91%
“…When groups 1 and 3 were compared, it was seen that they did not show such a strong adhesion as NB2CA. Hierholzer et al [22] also demonstrated that intestinal ischemia/reperfusion injury in rats results in a molecular and cellular inflammatory response within the intestinal muscularis and in a decrease in muscle contractions. As a result, this inflammatory response during ischemia-reperfusion has the effect of forming strong intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we investigated mediators that are specifically known to initiate leukocyte recruitment, to be involved in transplantation-associated problems and to modulate smooth muscle function in rodent models of ischemia/reperfusion and intestinal manipulation (24,25).…”
Section: Discussionmentioning
confidence: 99%